2021
DOI: 10.1101/2021.01.30.428333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust, sensitive, and quantitative single-cell proteomics based on ion mobility filtering

Abstract: Unbiased single-cell proteomics (scProteomics) promises to advance our understanding of the cellular composition of complex biological systems. However, a major challenge for current methods is their ability to identify and provide accurate quantitative information for low abundance proteins. Herein, we describe an ion mobility-enhanced mass spectrometry acquisition method, TIFF (Transferring Identification based on FAIMS Filtering), designed to improve the sensitivity and accuracy of label-free scProteomics. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…Most reported mass-spectrometry-based scProteomics technologies can be classified based upon whether they make use of isotopic labeling; i.e., they are either label-free or use isobaric labeling. In the label-free methods 5 10 , single cells are individually processed and analyzed with liquid chromatography-mass spectrometry (LC-MS). Ion current measurements (i.e., MS1 ion currents) are used to quantify protein abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Most reported mass-spectrometry-based scProteomics technologies can be classified based upon whether they make use of isotopic labeling; i.e., they are either label-free or use isobaric labeling. In the label-free methods 5 10 , single cells are individually processed and analyzed with liquid chromatography-mass spectrometry (LC-MS). Ion current measurements (i.e., MS1 ion currents) are used to quantify protein abundance.…”
Section: Introductionmentioning
confidence: 99%
“…On the MS side, gas-phase fractionation using ion mobility spectrometry (IMS) devices coupled to traditional LC–MS setups has proven to substantially increase ion selectivity and sensitivity by filtering out nonpeptide ions prior to MS analysis ( Cong et al, 2020 ; Greguš et al, 2020 ; Brunner et al, 2021 ; Stejskal et al, 2021 ; Woo et al, 2021a ). Using Nanodroplet Processing in One pot for Trace Sample (nanoPOTS) (see “Automated processing for small-volume samples”) sample preparation and optimized settings on a high field asymmetric IMS interface coupled to an Orbitrap Eclipse Tribrid MS identified over 1,000 protein groups from single HeLa and motor neuron cells ( Cong et al, 2020 ).…”
Section: Recent Advances In Low-input and Single-cell Proteomicsmentioning
confidence: 99%
“…Notably, the Slavov laboratory recently demonstrated that a handful of TFs could by identified and quantified by sc-MS in macrophages [58 ▪▪ ]. Finally, temporal trajectories were recently established from sc-MS data of murine macrophages during lipopolysaccharide stimulation [60]. Based on these new exciting results, it is entirely conceivable that, with further advances in sample processing, experimental design, and computational approaches, MS-based proteomics will soon permit large-scale proteome measurements in single cells, opening new doors to understanding transcriptional regulation of erythropoiesis and other dynamic cellular processes.…”
Section: Text Of Reviewmentioning
confidence: 99%